Preparation of N-Doped Mesoporous TiO2 Using Nitromethane as Nitrogen Source and Their High Photocatalytic Performance. Issue 5 (3rd May 2016) - Fang, Qian; Tang, Jianting; Zou, Huamei; Cai, Tiejun; Deng, Qian
Abstract : N-doped mesoporous TiO2 was successfully prepared by using CH3 NO2 as the nitrogen source and P123 as template. The materials were characterized by TEM, N2 sorption, XRD, XPS, UV-vis DRS, and TG-DTA techniques. The photocatalytic activity of N-doped TiO2 was tested in elimination of gaseous methanol, formaldehyde, and BTX (benzene, toluene and xylene). The obtained N-doped mesoporous TiO2 materials have better photocatalytic activity than commercial photocatalyst (Degussa P25). Moreover, the N-doped mesoporous TiO2 photocatalysts are easy to prepare and have stable performance, high photocatalytic activity and long lifetime.